Ekologi Administrasi dalam Kebijakan Ekonomi Berkelanjutan: Studi Kasus Pemerintah Daerah Gorontalo - Sri Yulianty Mozin; Romy Tantu; Intan Juleyka Halid (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the application of administrative ecology in the formulation and implementation of sustainable economic policies at the local government level in Gorontalo, Indonesia. Administrative ecology provides an analytical lens to understand the interaction between institutions, socio-cultural values, and environmental contexts that shape policy outcomes. The study is motivated by the challenges of balancing economic growth with environmental conservation and social equity in resource-dependent regions. Using a qualitative case study approach, data were collected through document analysis, field observations, and interviews with local stakeholders. Findings reveal that sustainable economic policy in Gorontalo is significantly influenced by administrative ecology factors, including institutional capacity, local leadership dynamics, and community participation. The integration of ecological, social, and economic considerations remains partial, often constrained by political cycles, limited financial resources, and fragmented inter-agency coordination. Nevertheless, innovative practices such as community-based resource management and multi-stakeholder collaboration have emerged as adaptive strategies. The study contributes to the literature on public administration and sustainable development by providing empirical evidence from Gorontalo. Practically, it highlights the need for strengthening institutional synergy, enhancing participatory governance, and aligning regional development plans with the principles of sustainable economics.